Formalisasi Syari’ah Islam Di Indonesia - Lilik Andaryuni (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2012)
Spirit to apply syariah Islam in various areas in Indonesia apparently never extinguished, and one of them is in NAD. Application of syariah Islam in Aceh actually parses various criticisms and arguments; in fact the case that the application of syariah Islam in NAD is a gift from the central government, because of there is a concern from central of NAD will separate from NKRI. Formalization (canonization) of Islam law is a way to safely the law of Islam. Therefore, the law of Islam that has been formalized in the form of regulation/canon, so that in the application caused no pros and cons from various parties, better prepared well, both in terms of material, readiness of human resources also the local readiness to execute it, thus caused no productive cons later.